MAQASHID AL-SYAR'IYYAH: - mardika, andi (State of Islamic Institute Langsa, 2021)
This article discusses the deteriorating environmental conditions globally from the point of view of maqashid sharia. Awareness of the importance of preserving and protecting nature is still not widely seen from the perspective of Islamic law. Using the reconstruction of Islamic law through a critical reading of maqashid sharia, this paper proposes the views: (1) The old jurisprudence does not accommodate environmental problems as a separate system in the field of study of legal objectives, (2) the exacerbation of the environmental crisis needs to be a concern for future studies of Islamic law, (3) Muslims need a comprehensive legal framework/guidelines on environmental issues through understanding the goals of Islam. In the end, this article argues that the study of Islamic law needs to enrich the discourse on environmental sustainability through the reconstruction of maqashid sharia.